Effect of irrigation water withdrawal on the hydrology of the Lake Tana sub-basin - Taye, Meron Teferi; Haile, Alemseged Tamiru; Fekadu, A. G.; Nakawuka, P. (Elsevier, 2021)
Study region: The Lake Tana sub-basin, upper Blue Nile, Ethiopia. Study focus: The Lake Tana sub-basin is one of the agricultural growth corridors for Ethiopia’s ambitious plan to expand irrigation. Despite the booming irrigation activities in the sub-basin, limited information exists on the rate of irrigation expansion and its impact on the water balance of the sub-basin. This study collected and organized smallholder irrigation data in the subbasin to identify the actual irrigated area, the abstracted irrigation water, and its implications on seasonal water availability. The area under small-scale irrigation was estimated through data obtained from ’woredas’ (districts) databases. Crop patterns were obtained through field surveys. Irrigation water abstracted at daily timescale was measured. New hydrological insights for the Region: In the sub-basin, 38,694 ha was under small-scale irrigation in 2020/21. Surface water is the dominant water source, and it supplies about 80% of irrigation withdrawal. Water abstraction for small-scale irrigation is about 430 MCM per dry season (~50% of dry season flow). The eastern side of the sub-basin faces water shortages as the dry season flow is not sufficient for irrigation. With the prospects of more irrigation expansion, small-scale irrigation water withdrawals pose concerns of water scarcity at local level and to the water balance of the sub-basin. Hence, there is urgent need for adaptive management of the small-scale irrigation effect on the sub-basin’s hydrology.